Improvement of bovine pestiviral diagnosis by the development of a cost-effective method for detecting viral RNA in fresh specimens and samples spotted in filter papers - Favaro, Paula Melisa (2023)
Bovine pestiviruses are the causative agents of bovine viral diarrhea, a disease thatcauses severe economic losses in cattle. The aim of this study was to improve their diagnosisby developing a RT-qPCR to detect bovine pestiviruses A, B and H; and to set up a protocolfor collecting, shipping and preserving bovine pestiviral RNA on filter papers. The developedRT-qPCR showed high sensitivity in detecting these viruses in different matrices: viral stocks,semen and serum samples. With regard to the possibility of using the technique to test serumpools, it was possible to identify a positive serum sample within a pool containing 30 sera.In addition to evaluating the qPCR from fresh samples, the use of filter papers to sow bovinesamples was analyzed. The sampling method on two different filter papers using bovine blooddrops was a useful alternative for diagnostic purposes and allowed to preserve pestiviral RNAfor up to 12 months under refrigeration.